Evaluation of the clinical utility of maximum intensity projections of 3D contrast‐enhanced, T1‐weighted imaging for the detection of brain metastases. Issue 5 (7th August 2020) - Hainc, Nicolin; Federau, Christian; Tyndall, Anthony; Mittermeier, Andreas; Bink, Andrea; Stippich, Christoph; Schubert, Tilman
Abstract: Background: To visualize and assess brain metastases on magnetic resonance imaging, radiologists face an ever‐increasing pressure to perform faster and more efficiently. The usage of maximum intensity projections (MIPs) of contrast‐enhanced T1‐weighed (T1ce) magnetization‐prepared rapid acquisition with gradient echo (MP‐RAGE) images proposes to increase reading efficiency by increasing lesion conspicuity while reducing in the number of images to be reviewed. Aim: To assess if MIPs save reading time and achieve the same level of diagnostic accuracy as standard 1 mm T1ce images for the detection of brain metastases. Methods: Forty‐four patients were included in this retrospective study. Axial reformations of T1ce MP‐RAGE (TR/TE = 2300/2.25 ms, resolution = 1 mm 3 ) images were analyzed and post‐processed into 5 and 10 mm MIPs. Two readers evaluated the randomly assorted images and recorded reading time. Reading time differences were analyzed using the Wilcoxon test, and inter‐reader statistics were performed using Bland–Altman plots. Results: About 22.5 61.2 s/study and 43.8 ± 159.9 s/study were saved using 5 and 10 mm MIPs, respectively. Combined average sensitivity was 92.0% for 5 mm MIPs and 86.3% for 10 mm MIPs compared to standard 1 mm axial slices, with an average rate of 0.98 and 0.57 false positives per study, respectively Conclusion: While 5 mm and 10 mm T1ce MP‐RAGE MIPs showed a clinical benefit in reducing reading times for evaluation of brain metastases, they should be used in conjunction with standard 1 mm images for best sensitivity and specificity, a practice which possibly annuls their benefit.